Automatic Detection of Trees using Airborne LiDAR Data Based on Geometric Characteristics - dos Santos, Renato César [UNESP]; da Silva, Matheus Ferreira [UNESP]; Alencar, Cleber Junior; Galo, Mauricio [UNESP] (Copernicus Publications, 2024)
One of the essential factors in analyzing urban environments is the presence of trees. Thus, the development of automatic or semiautomatic tree detection strategies is important for monitoring and providing data for municipal authorities' planning efforts. In this context, we propose an automatic method for detecting trees using LiDAR data collected by airborne platforms. The proposed strategy uses the omnivariance as a key attribute, which is estimated locally from eigenvalues. Additionally, it utilizes an adaptive process to determine the optimal radius, followed by successive filtering based on the majority filter and mathematical morphology operators. The effectiveness of the proposed approach was evaluated on six study areas from two distinct datasets (Presidente Prudente/Brazil and Palmerston/New Zealand). In general, the results indicate a completeness rate around 99% and a correctness rate around 91%, resulting in an average Fscore of 95%. These findings suggest that the proposed approach has potential to detect trees in urban regions using airborne LiDAR data. Compared to related works, the proposed strategy tends to have a better result in terms of completeness.
Keywords: 3D Point Cloud; LASER Scanning; Photogrammetry; Remote Sensing; Tree Extraction; Urban Forests